102 Ultrasound guided paracentesis in a hospice setting: a case series. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Tinker, Andrew; Russon, Lynne; Kane, Christopher
Abstract : Background: Ultrasound guided paracentesis is a safe and effective methods of managing ascites caused by malignancy or cirrhosis. It has traditionally been performed in hospital and often requiring admission for one or more nights. Following training in ultrasound and gaining experience in ultrasound guided paracentesis at our local hospital trust, we evaluated the introduction of a hospice based paracentesis day-case programme. Methods: We undertook a prospective evaluation of the service over 3 years in specialist palliative care patients referred for assessment of possible ascites and where indicated draining ascites in a hospice setting, including patient feedback collected approximately a week after the procedure. Results: 85 assessments were performed for possible ascites (58% non-hepatocellular cancer, 31% cirrhosis ± malignancy, 1% other), in 58 different patients. 45 patients were assessed as having paracentesis suitable for drainage in the hospice setting. This led to 36 successful ultrasound guided paracentesis procedures performed in the hospice inpatient unit (9 patients did not have paracentesis as not very symptomatic and/or too unwell). 21 were performed on a day case basis, 11 as part of a longer admission for symptom control or end of life care, and only 4 (16% of admissions for paracentesis) requiring an overnight stay for the procedure. There were no complications 64% of patients completed feedback a week later. 23/23 (100%) patients would be happy to have the procedure repeated in the hospice setting if required. 16/23 (70%) said paracentesis greatly helped symptoms, and 6/23 moderately (26%) Conclusions: It is practical and useful to include ultrasound in assessment of possible ascites in a hospice setting, and to use ultrasound guided paracentesis for day case, and existing inpatients in a hospice setting. This leads to reduced hospital attendance/admission, and it is an acceptable alternative to patients.